Evaluation of SPMI-Based Education Quality Supervision Programs in Rural and Remote Public Elementary Schools - Badarudin Badarudin; Ahmad Tohri; Lalu Parhanuddin; Tatan Tatan; Muhammad Ali (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2025)
This study aims to analyze the implementation of context evaluation, input, process, and product in the SPMI-based education quality supervision program evaluation activities at public elementary schools in East Lombok Regency. This study employed a qualitative approach using the CIPP model. The subjects of this study consisted of key informants, namely principals, and supporting informants, including teachers, school education quality assurance teams, and students. Data were collected through in-depth interviews, observations, documentation, and literature studies. The data analysis technique utilized an interactive analysis model comprising three main components: data reduction, data presentation, and drawing conclusions or verification. The results show that input aspects face challenges, particularly in teacher availability and infrastructure, while financial support is sufficient. The process aspect demonstrates improvements through the consistent implementation of the SPMI cycle, supported by principals, teachers, and TPMPS teams. Product evaluation indicates progress in several National Education Standards, including graduate competencies and school management, although issues persist in content and infrastructure standards. Overall, the program’s effectiveness depends on strong input quality and process execution to produce optimal educational outcomes in a sustainable and integrated manner.